An Asset-Based Community Assessment of Physical Activity at Fort Riley Installation - O'Neal, Joshua (My University, 2014)
Obesity may be viewed as excess body fat that conveys increased risk for adverse health outcomes. Historically, obesity was rarely seen in children and adults (Haslam, 2007). It was not until the 20th century that obesity became a common issue among Americans. Today, more than one-third of U.S. adults (35.7%) are obese (Centers for Disease Control and Prevention, 2013b). Furthermore, obesity has more than doubled in children (ages 6–11) and has tripled among adolescents (ages 12–19) in the past 30 years (Centers for Disease Control and Prevention, 2013a). Numbers are even concerning when overweight (e.g., BMI ranging 25–29.9) and obese (e.g., BMI of 30 or greater) statistics are combined. According to the 2008 Physical Activity Guidelines for Americans, as a minimum, all adult Americans should engage in moderate-intensity aerobic physical activity (e.g., brisk walking) for at least 150 minutes per week or engage in vigorous intensity aerobic physical activity (e.g. running) for at least 75 minutes per week or a combination of the two (U.S. Department of Health and Human Services [USDHHS], 2008). All moderate and vigorous intensity aerobic physical activity should be performed for at least ten minutes in duration. Furthermore, all adults should incorporate muscle strengthening exercises (e.g. lifting weights, pushups, yoga) at least twice a week. These recommendations have been established to prevent further weight gain and to maintain health. In order to increase health benefits, The USDHHS recommends performing twice as much of each type of aerobic physical activity per week (i.e., 300 minutes of moderate intensity or 150 minutes of vigorous intensity) (USDHHS, 2008). Furthermore, children and adolescents should receive 60 minutes (1 hour) of physical activity per day. Physical activity should be at either moderate or vigorous intensity and should include vigorous intensity physical activity at least 3 days a week (USDHHS, 2008). In addition to their 60 minutes of physical activity, children and adolescents should perform muscle strengthening physical activity (e.g., climbing trees, tug-of-war) on at least 3 days per week (USDHHS, 2008). Furthermore, bone strengthening activity should be performed on at least 3 days per week (e.g., jump rope, basketball). Obesity has been linked to specific socioeconomic status (SES) such as race/ethnicity, income, education, and gender (Sobal & Stunkard, 1989; McLaren, 2007). Today, there is no question that the rates of obesity in the U.S. follow a socioeconomic gradient (Drewnowski & Specter, 2004). This has become ever so evident in the U.S. Armed Forces, where obesity is a matter of national security. The military views obesity as a significant military medical concern because it is associated with decreased military operational effectiveness (e.g., physical fitness) and may increase the chances of becoming injured (Armed Forces Health Surveillance Center, 2011a). Thus, soldiers who are classified as being obese may become a liability to the Army and are discharged if they cannot meet APFT requirements or weight standards. In 2012, the Army kicked out 1,625 soldiers for not meeting their APFT requirements as well APFT weight standards, which was 15 times greater than the number discharged for the same reason in 2007 (Armed Forces Health Surveillance Center, 2011b). The current rate of obesity for the Army is 16.1% (Barlas, Higgins, & Pflieger, 2013). Obesity has also become an increasing concern among U.S. Military families. The current estimated cost of obesity to the Military Health System (MHS) is approximately $2 billion per year (The Military Health System Must Deal with Obesity, 2009), which is a significant burden for the US Department of Defense. Even though there are a number of resources available for military families to maintain a healthy lifestyle, obesity has still increased. There are unique barriers that contribute to military life, which may affect health behaviors. For example, deployment of military members significantly affects the emotional and physical wellbeing of military families (Pincus, House, Christennson, & Adler, 2001). Many military families are also constantly relocating (on average every two years) due to the high rotation cycles, which may cause a lack of stability in their lives because they never have time to fully adjust to their new environment. In addition, family members may not have enough time to build a social network within their new community, which also contributes to feeling a lack of stability. In 2010, a government article was release by a group of military leaders titled, “Too Fat to Fight.” The primary focus of the article was a call to Congress to pass laws that would remove junk food from schools and military installations in order to decrease obesity in Americans (Mission: Readiness Military Leaders for Kids, 2010). In 2012, another article was released titled, “Still Too Fat to Fight,” which was written by the same group. This article was a plea to Congress to take strong actions in preventing obesity. Again, the article had the same request to eliminate junk food from schools and military installations (Mission: Readiness Military Leaders for Kids, 2012). There is a continual failure to prevent increases in obesity of Americans. On all military installation there is a strong focus on healthy nutrition in order to combat obesity. However, little emphasis is placed on promoting physical activity for both soldiers and family members within the community. For soldiers, performing physical activity may not be a concern, because they are required to perform one hour of PT three days per week, up to five days per week (depending on their commanding officer’s preferences). A report by Barlas and associates (2013) surveyed health related behaviors of active duty personal, and found that 35.8% of Army personnel reported 150 minutes or more per week of moderate activity, and 46.3% reporting 150 minutes or more of vigorous physical activity per week; meeting and exceeding current physical activity recommendations (Figure 3; Barlas et al., 2013). In addition, 33.0% of Army personnel reported 300 minutes or more of moderate physical activity per week on average. However, their physical activity levels may not be meeting their caloric intake, which may help explain the increase in overweight and obese soldiers. As well, over 1/3 of soldiers are not meeting weekly recommended levels of moderate (36.8%) and/or vigorous (46.3%) physical activity. To my knowledge, there has been no research conducted which looks at the physical activity levels of military families. There has been some recent research on physical activity levels of veterans with disabilities and health conditions (e.g., type 2 diabetes; Bouldin & Reiber, 2012). As well, little to no research has been conducted on community assets building on an Army installation. Needless to say, in order to reduce obesity rates among active duty soldiers and their families we must look beyond nutritional interventions and start assessing the need for greater physical activity levels.
Keywords: Fort Riley; Obesity; Asset mapping; Public Health (0573)